2009
DOI: 10.1007/978-3-211-98811-4_52
|View full text |Cite
|
Sign up to set email alerts
|

The Role of eNOS in Vascular Permeability in ENU-Induced Gliomas

Abstract: Brain edema in gliomas is an epiphenomenon related to blood-brain-barrier (BBB) breakdown in which endothelial nitric oxide synthase (eNOS) plays a key role. When induced by vascular endothelial growth factor (VEGF), eNOS synthesizes nitric oxide that increases vascular permeability. We investigated the relationship between eNOS, VEGF and BBB dysfunction in experimental gliomas.Tumors were produced in Sprague-Dawley rats by transplacentary administration of Ethylnitrosourea (ENU). Immunoexpression of eNOS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…It has been suggested that increased permeability may be related to any combination of the following factors: breakdown of the astrocyte-vascular endothelial interaction and loss of vascular pericyte coverage [52], increased eNOS synthesis secondary to VEGF secretion from cancer cells [53], the presence of inflammatory cytokines such as TGFβ [54], the process of angiogenesis [55], and the dysregulation of tight junction proteins in the BTB [56]. Changes in vascular permeability may actually be a representation of all factors at one given time in the local tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that increased permeability may be related to any combination of the following factors: breakdown of the astrocyte-vascular endothelial interaction and loss of vascular pericyte coverage [52], increased eNOS synthesis secondary to VEGF secretion from cancer cells [53], the presence of inflammatory cytokines such as TGFβ [54], the process of angiogenesis [55], and the dysregulation of tight junction proteins in the BTB [56]. Changes in vascular permeability may actually be a representation of all factors at one given time in the local tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cigarette smoke has been shown to lead to cerebrovascular vasodilation through sympathetic activation. Nicotine activates nicotine receptors, which leads to the acetylcoline-dependent release of NO from the vascular endothelium [47,48] through activation of endothelial nitric oxide synthase (eNOS) [49]. NO is one of the major endothelium-derived relaxing factors, which plays an active role in regulating microvascular tone and the cerebral blood flow under normal and pathological conditions [50].…”
Section: Pathophysiology Of Bbb Endothelial Cellsmentioning
confidence: 99%
“…NO activity has been extensively studied in tumor biology (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). It appears to be involved in all phases of carcinogenesis (12).…”
Section: Effects Of Nitric Oxide Synthase Deficiency On a Disintegrinmentioning
confidence: 99%
“…eNOS-derived NO has been shown to enhance angiogenesis in gliomas (14). Low grade gliomas demonstrate constitutive expression of eNOS in vessel endothelial cells and astrocytes, whereas malignant gliomas demonstrate overexpression of eNOS in aberrant vessels (15). Furthermore, studies have demonstrated that eNOS-deficient (eNOS -/-) mice may be resistant to chemical carcinogenesis (16) and platelet-derived growth factor-induced gliomagenesis (17).…”
Section: Effects Of Nitric Oxide Synthase Deficiency On a Disintegrinmentioning
confidence: 99%